The Pathogenesis of Ischemia-Reperfusion Induced Acute Kidney Injury Depends on Renal Neutrophil Recruitment Whereas Sepsis-Induced AKI Does Not - Li, Zhenhan; Ludwig, Nadine; Thomas, Katharina; Mersmann, Sina; Lehmann, Martin; Vestweber, Dietmar; Pittet, Jean-Francois; Gomez, Hernando; Kellum, John A.; Rossaint, Jan; Zarbock, Alexander (Frontiers in Immunology, 2022)
Acute kidney injury (AKI) may be induced by different causes, including renal ischemia-reperfusion injury and sepsis, which represent the most common reasons for AKI in hospitalized patients. AKI is defined by reduced urine production and/or increased plasma creatinine. However, this definition does not address the molecular mechanisms of different AKI entities, and uncertainties remain regarding distinct pathophysiological events causing kidney injury in the first place. In particular, sepsis-induced AKI is considered not to be associated with leukocyte infiltration into the kidney, but a direct investigation of this process is missing to this date. In this study, we used two murine AKI models induced by either renal ischemia-reperfusion injury (IRI) or cecal ligation and puncture (CLP) to investigate the contribution of neutrophils to tissue injury and kidney function. By using VEC-Y731F mice, in which neutrophil recruitment is impaired, we analyzed the specific contribution of neutrophil recruitment to the pathogenesis of IRI- and CLP-induced AKI. We observed that the degree of renal injury evaluated by plasma creatinine, urinary biomarkers and histological analyses, following IRI-induction was dependent on neutrophil migration into the kidney, whereas the pathogenesis of CLP-induced AKI was independent of neutrophil recruitment. Furthermore, plasma transfer experiments suggest that the pathogenesis of CLP-induced AKI relies on circulating inflammatory mediators. These results extend our knowledge of the AKI pathogenesis and may help in the development of prophylactic and therapeutic treatments for AKI patients.